The use of scientific information in setting ambient air standards. - Jordan, B C (1983)
The Clean Air Act, as amended in 1977, requires periodic review and revision of all national ambient air quality standards (NAAQS) to insure that they are based on the latest scientific information. This article presents an overview of how EPA currently reviews and establishes NAAQS. The role of scientific information and expertise in the process is illustrated by a review of several key issues faced in the development of the proposed revisions to the carbon monoxide NAAQS. Finally, a risk analysis framework being developed within EPA's Office of Air Quality Planning and Standards for possible future use in NAAQS reviews is described. The principal objective of the risk analysis framework is to provide more formal treatment of uncertainties in the scientific data base.